Baltic Sea ecosystem-based management under climate change: Synthesis and future challenges - Blenckner, Thorsten (Ambio, 2015)
Ecosystem-based management (EBM) has emerged as the generally agreed strategy for managing ecosystems, with humans as integral parts of the managed system. Human activities have substantial effects on marine ecosystems, through overfishing, eutrophication, toxic pollution, habitat destruction, and climate change. It is important to advance the scientific knowledge of the cumulative, integrative, and interacting effects of these diverse activities, to support effective implementation of EBM. Based on contributions to this special issue of AMBIO, we synthesize the scientific findings into four components: pollution and legal frameworks, ecosystem processes, scale-dependent effects, and innovative tools and methods. We conclude with challenges for the future, and identify the next steps needed for successful implementation of EBM in general and specifically for the Baltic Sea.